Mathematical model of distal radius orientation - Chen, Cheng-Kuang; Wu, Tai-Yin; Liao, Yu-Ciao; Fuh, Chiou-Shann; Chen, Kuan-Hao; Weng, Pei-Wei; Wang, Jr-Yi; Chen, Chih-Yu; Huang, Yu-Min; Chen, Chung-Pei; Chu, Yo-Lun; Yeh, Kuei-Lin; et al. (Frontiers in Surgery, 2022)
Distal radius orientation is important in evaluating Colles' fracture. In most cases, the wrist was protected by a bandage, splint, or cast. Therefore, it was difficult for the radiology technician to take perfect anteroposterior and lateral view radiographs. In this study, we build a mathematical model and calculate the pronation angle needed to produce dorsal tilt, which is a volar tilt in a perfect lateral view radiograph. The formulas are all incorporated into Excel to facilitate usage.